Protecting consumers against unfair contract terms in Malaysia: The Consumer Protection (Amendment) Act 2010 - Amin, Naemah (2012)
Consumers enter into various types of contract for the supply of goods or services in their everyday life. In most cases these contracts contain terms which are more favourable to traders but unfair to the consumers. A standard form contract designed by the traders is the common contract where unfair terms can be expected to be found. Unfair terms particularly in the form of exemption clauses can also be found or printed in the receipts, invoices and other sale documents. These terms may operate extremely harshly against the consumers because their rights may be limited or restricted or denied all together. Malaysian consumers have been haunted with this issue for a long time even after the introduction of the Consumer Protection Act (CPA) in 1999 since the issue has not been properly tackled by the Act. Nonetheless this major loophole in the Malaysian consumer protection law has recently been rectified by the CPA (Amendment) Act 2010. It is interesting to note that the Amendment has adopted the Indian Law Commission Report on Unfair (Procedural & Substantive) Terms in Contract (2006) which divides unfairness into ‘procedural’ and ‘substantive’ unfairness. Such a division has not been done in any country so far. This article evaluates the extent to which provisions on procedural unfairness and substantive unfairness under a new Part IIIA of the CPA provide better protection to consumers in terms of getting fair bargain.